Drug discovery for epigenetics targets. Issue 4 (April 2022) - Holdgate, Geoffrey A.; Bardelle, Catherine; Lanne, Alice; Read, Jon; O'Donovan, Daniel H.; Smith, James M.; Selmi, Nidhal; Sheppard, Robert
Highlights: Epigenetic changes modify genetic information without altering the DNA sequence. Epigenetics related proteins are classified into readers, writers and erasers. Dysregulation of the epigenome is associated with a number of diseases. Screening and rational design have been successfully applied to epigenetic targets. Abstract: Dysregulation of the epigenome is associated with the onset and progression of several diseases, including cancer, autoimmune, cardiovascular, and neurological disorders. Members from the three families of epigenetic proteins (readers, writers, and erasers) have been shown to be druggable using small-molecule inhibitors. Increasing knowledge of the role of epigenetics in disease and the reversibility of these modifications explain why pharmacological intervention is an attractive strategy for tackling epigenetic-based disease. In this review, we provide an overview of epigenetics drug targets, focus on approaches used for initial hit identification, and describe the subsequent role of structure-guided chemistry optimisation of initial hits to clinical candidates. We also highlight current challenges and future potential for epigenetics-based therapies.